Loose Monetary Policy and Corporate Investment of Manufacturing Firms in the Czech Republic - Veronika Kajurová; Dagmar Linnertová (Review of Economic Perspectives, 2018)
The aim of the paper is to evaluate the effects of loose monetary policy on corporate investment of manufacturing firms in the Czech Republic during the period between 2006 and 2015. The main focus of the paper is on the effect of low interest rates on investment activity of Czech firms; additionally, the effects of interactions between interest rate and other firm-specific variables are investigated. The results indicate that corporate investment is positively associated with firm size, investment opportunities, and long term debt. Also, a negative effect of the cash position is found. Further, the findings show that monetary policy is a significant determinant of firm investment activity: when the monetary policy is loose, investment is positively affected. Furthermore, differences in the determinants of investment between highly and low leveraged firms were revealed.
Keywords: 330; balance sheet channel; corporate investment; loose monetary policy; low interest rates